Extrajudicial Market Conflict Resolution - Permata Jali Dimasiosz; Afrizal Afrizal; Elfitra Elfitra (LPPM Universitas PGRI Sumatera Barat, 2023)
The spatial conflict that occurred at Pasar Raya Padang involved parking attendtants, street vendors and shop traders who fought to control the same space. Lefebvre's theory is use to describe the struggle for space as a cause of conflict and Benda-Beckmann's theory to explain behavior in using conflict resolution forums. Through a qualitative approach and data analysis based on primary and secondary sources, this research evaluates the effectiveness of conflict resolution methods adopted by the City Government and seeks alternative solutions through external forums such as the DPRD, Ombudsman and Komnas HAM. The results show that conflict resolution and regulatory enforcement carried out by the City Government are not optimal, triggering conflict escalation. This has not yet reached a resolution, but external forums such as the DPRD, Ombudsman and Komnas HAM play an important role in supervising the implementation of regulations by the City Government and encouraging conflict resolution. Apart from that, this research also found that even though the cancellation or substantive changes to the rules have not been made, this external forum plays an important role in ensuring the safety of trading in the market. This shows that resolving space conflicts does not only involve changing rules, but also monitoring the implementation of existing rules. In terms of implementation, the results can be a recommendation for city governments to involve external forums in resolving spatial conflicts, especially in traditional markets. The results can also be a reference for other researchers who are interested in studying spatial conflict in a similar context. The novelty of this research lies in the discovery of the importance of external forums in monitoring the implementation of policies and conflict resolution mechanisms by city governments, something that has not been found in many previous studies examining spatial conflicts in traditional markets.